2017
DOI: 10.1002/2016jb013040
|View full text |Cite
|
Sign up to set email alerts
|

Strength anisotropy of shales deformed under uppermost crustal conditions

Abstract: Conventional triaxial tests were performed on three sets of samples of Tournemire shale along different orientations relative to bedding (0°, 45°, and 90°). Experiments were carried out up to failure at increasing confining pressures ranging from 2.5 to 160 MPa, at strain rates ranging between 3 × 10−7s−1 and 3 × 10−5s−1. This allowed us to determine the entire anisotropic elastic compliance matrix as a function of confining pressure. Results show that the orientation of principal stress relative to bedding pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
3
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 47 publications
5
62
3
2
Order By: Relevance
“…For slow strain rate the mechanism seem to be more ductile with plastic mechanisms such as mineral reorientation and delayed fracture localization. All these mechanisms are also supporting the conclusions made in Bonnelye et al [].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…For slow strain rate the mechanism seem to be more ductile with plastic mechanisms such as mineral reorientation and delayed fracture localization. All these mechanisms are also supporting the conclusions made in Bonnelye et al [].…”
Section: Discussionsupporting
confidence: 91%
“…At the highest confining pressure ( P c =80 MPa, Figure c), the previous trend is enhanced: wave velocities measured along raypaths with a small angle relative to bedding decrease, while those measured along raypaths with a large angle relative to bedding increase, so that we observed anisotropy reversal before failure which illustrates fully the increasing role of plastic deformation processes with increasing confinement. This was also confirmed by the shape of the axial strain‐deviatoric stress curves presented in [ Bonnelye et al , ]. When looking closer before and after failure (Figures a and b), we see that the drop of elastic wave velocities occurs along certain raypath only several hours after failure.…”
Section: Resultssupporting
confidence: 85%
“…Moreover, the rupture continued to develop until the specimen became completely destroyed. In comparison to previous studies [30,31], the failure strength in this study was found to be much larger.
Figure 5.Triaxial stress–strain curve of shale under a confining pressure of 20 MPa.
…”
Section: Experimental Results and Studycontrasting
confidence: 92%
“…In the case of shales, the bedding planes provide such a plane of weakness, but due to the anisotropic nature of the shale matrix, it is worth investigating the failure strengths of the bedding‐parallel and bedding‐perpendicular samples separately. McLamore and Gray (), Sone and Zoback (), and Bonnelye et al () all find samples of shales to support a slightly higher maximum differential stress in the bedding‐parallel orientation than in the bedding‐perpendicular orientation over a range of confining pressures. Ambrose () found the same in Bossier shale but found no difference between the two orientations in the Vaca Muerta shale.…”
Section: Discussionmentioning
confidence: 96%